2008
DOI: 10.1080/02841850802438504
|View full text |Cite
|
Sign up to set email alerts
|

Palpable breast masses with probably benign morphology at sonography: can biopsy be deferred?

Abstract: Background: When a palpable breast mass is detected, a biopsy is usually performed even if the mass reveals probably benign morphologic features on imaging, as there is relatively little data reporting the outcome of such breast masses. Purpose: To determine the negative predictive value for sonographic evaluation of palpable breast masses with probably benign morphology, and to assess whether follow-up may be an acceptable alternative to immediate biopsy. Material and Methods: Of the 1399 sonograms of palpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 37 publications
2
52
0
2
Order By: Relevance
“…Graf et al (3) detected multiplicity in 7.6% of 409 women in their study. Park et al (11) found multiple BI-RADS 3 masses on US in 23 of 274 women. Multiplicity, especially multiple bilateral category 3 masses, has been shown to decrease the likelihood of malignancy of circumscribed masses detected on mammography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graf et al (3) detected multiplicity in 7.6% of 409 women in their study. Park et al (11) found multiple BI-RADS 3 masses on US in 23 of 274 women. Multiplicity, especially multiple bilateral category 3 masses, has been shown to decrease the likelihood of malignancy of circumscribed masses detected on mammography.…”
Section: Discussionmentioning
confidence: 99%
“…In follow-up studies, BI-RADS category 3 masses have generally been assessed using a combination of mammography and US (2,6,11). However, this combination may not always be available in practice.…”
Section: Discussionmentioning
confidence: 99%
“…18 The negative predictive value of sonography for palpable noncalcifi ed breast masses with probably benign morphology is high at 99.4% (with a false negative rate therefore of just 0.6%). 19 This has led researchers to suggest that such lesions could be managed in a similar fashion to non-palpable BI-RADS 3 lesions, with short-term imaging follow-up as opposed to immediate biopsy. 19,20 The sensitivity of ultrasonography is not age dependent as with mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Zaniechanie dalszych procedur diagnostycznych można rozważyć u osób, u których na podstawie badania przedmiotowego i USG nie potwierdzono obecności zmian w piersi, oraz u chorych ze zmianami (zarówno palpacyjnymi, jak i niepalpacyjnymi), które w kolejnych badaniach ultrasonograficznych mają charakter prostej torbieli lub niepodejrzanych zmian litych o śred-nicy poniżej 1 cm [21,22].…”
Section: Postępowanie Diagnostyczneunclassified